Knowledge, attitudes and practices regarding HIV/AIDS among senior high school students in Sekondi-Takoradi metropolis, Ghana - Seraphine M. Dzah; Elvis E. Tarkang; Prosper M. Lutala (AOSIS, 2019)
Background: In Ghana, youths aged 15-24 years constitute the group most vulnerable to HIV infection. Inadequate knowledge, negative attitudes and risky practices are major hindrances to preventing the spread of HIV. Aim: This study sought to investigate the knowledge, attitudes and practices regarding HIV/AIDS among senior high school (SHS) students. Setting: Sekondi-Takoradi metropolis, Ghana. Methods: A descriptive, cross-sectional design was adopted, using a validated self-administered questionnaire, to collect data from a stratified sample of 294 senior students selected from three participating high schools in August 2017. The data collected were analysed using Stata version 12. Descriptive and inferential statistics were at a significance level of 0.05. Results: Among the participants, 61.6% had good knowledge about HIV/AIDS, 172 (58.5%) showed positive attitudes towards people living with HIV (PLHIV) and 79.1% reported HIV-related risky practices. We found a significant association between age and attitudes (p < 0.05). Poor knowledge was associated with being Muslim (aOR = 1.51 and 1.93; CI 1.19-1.91; p = 0.00) and being a student from school 'F' senior high school (F SHS) (aOR = 1.93; CI 1.71-2.18; p = 0.00). Bad attitude towards PLHIV and HIV was associated with ages 15-19 years (aOR = 3.20[2.58-3.96]; p = 0.03) p confirmed; and single marital status (aOR = 1.79[1.44-2.23]; p = 0.00). Bad practices were associated with ages 15-19 years (aOR = 1.72[1.41-2.11]; p = 0.08), belonging to the Akans ethnic group (aOR = 1.57[1.26-1.97]; p = 0.00) or being single (aOR = 1.79[1.44-2.23]; p = 0.00). Associations between misconceptions and HIV transmission were found: HIV can be transmitted by a handshake (aOR = 3.45[2.34-5.68]; p = 0.000), HIV can be cured (aOR = 2.01[2.12-5.04]; p = 0.004) and HIV/AIDS can be transmitted by witchcraft (aOR = 3.12[3.21-7.26]; p = 0.001). Conclusion: Participants generally had inadequate knowledge regarding HIV/AIDS, manifested negative attitudes towards PLHIV and also engaged in risky practices that might predispose them to HIV transmission. Our findings underscore the need for culturally adapted and age-oriented basic HIV information for youths in the metropolis on misconceptions about HIV transmission, negative attitudes of students towards PLHIV as well as the risky practices of students regarding HIV.